Information and Prices with Capacity Constraints - Lester, Benjamin (American Economic Review, 2011)
In the theoretical literature on consumer search, one conclusion is nearly universal: as buyers become better able to observe and compare prices ex ante, sellers will set lower prices in equilibrium. In this paper, I examine a standard consumer search model with one small – yet often relevant – additional restriction: I assume that sellers are capacity constrained. In this environment, I illustrate that the conventional wisdom regarding information and prices does not necessarily hold: having more informed consumers can lead to a decrease in prices, have no effect at all, or even lead to an increase in prices.